PENCATATAN PERUBAHAN DIREKSI DI KEMENTERIAN TERKAIT SEBAGAI DASAR PENYELESAIAN SENGKETA KEWENANGAN DIREKSI - Maleakhi W. Sitompul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Research on the recording of changes to directors in the relevant Ministry, namely the Ministry of Law and Human Rights, aims to examine whether the authorized Directors in a company are Directors registered at the Ministry of Law and Human Rights. In addition, it is also to examine whether the provisions of Law no. 40 of 2007 concerning Limited Liability Companies and / or the Company's Articles of Association is sufficient to resolve disputes of authority in the event of a dispute regarding the composition and number of directors in a company, which one has the right to act against other parties. Disputes regarding the composition and authority of the Board of Directors in a limited liability company often become disputes in court, even though Indonesia's positive legal provisions have provided clear and firm rules about who the Board of Directors can represent in and out of court. Based on research, it can be seen that the starting point is from the provisions in Law No. 40 of 2007 Articles 29 and 98, changes in the members of the board of directors can only be effective for third parties, as from the date the changes are recorded in the Company Register by the Minister of Law and Human Rights in accordance with Law No. 40 of 2007 Articles 29 and 98.